Prevalence of Helicobacter Pylori Isolated from Patients with Irritable Bowel Syndrome - M. Hamid, Daniah; AlChalabi, Rawaa; A. Abdul Jabbar, Fatimah; N. Aljanabi, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
One hundred seventy-two stool samples of suspected patients with irritable bowel syndrome were examined by H. pylori Ag Strip to detect the positive cases by using the bioNexia Ag kit (USA). Sixty-one patients were infected with H. pylori, while one hundred and eleven of them were negative patients for H. pylori and had irritable bowel syndrome and were taken as a control group. This study lasted from the period of 1st January 2017 to 1st May 2017 at Thatching Hospital/Medicine City. The result showed that there was no significant difference between the positive age cases (35.68 ±37.04) and the negative control (P>0.05). While the results showed that there was a highly significant difference among the age groups < 10 years, 4 (5.7%), and the negative control group, 13 (11.7%); 10-30 years, 24 (38.5) % compared with the control group, 23 (20.7%); 31-50 years, 21 (36.1%) compared with the control group, 52 (46.8%); and 51-70 years, 12 (19.7%) in comparison with the control group, 23 (20.7%), respectively (P < 0.01). The results also showed that there was no significant difference between the male gender 30 (48.4%) compared to the control group 45 (40.1%) and between the female gender 31 (51.6%) in comparison with the control group 57 (59.9%) (P > 0.05). In regard to the clinical symptoms of the situated groups, 61 (100%) compared to the control group 46 (42.4%). The current study indicated a highly significant difference between the patients with abdominal pain, 36 (59.0%), and the control group, 42 (38.3%), and between irritable bowel syndrome, 61 (100%), and the control group, 46 (42.4%) (P < 0.01). While there was a nonsignificant difference between patients with diarrhea, 17 (30.3%), compared to the control group, 28 (25.7%), and between patients with vomiting, 36 (59.0%), in comparison with the control group, 42 (38.3%), and between patients with weight loss, 11 (18.0%), compared with the control, 16 (14.0%), (P > 0.05).